KEMAMPUAN INTELEKTUAL, KEBUTUHAN BERPRESTASI, DAN PERFORMANSI KERJA DI PERUSAHAAN ALAT BERAT - Mulyani, Siti (Universitas Ahmad Dahlan, 2010)
This study was aimed to test empirically the correlation between intellectual ability and need achievement with work performance. The hypothesis posed in this study were: 1) there was correlation between intellectual ability and need achievement with work performance; 2) there was correlation between intellectual ability and work performance; 3) there was correlation between need achievement and work performance. This study involved 16 subjects of parts sales service in Heavy Equipment Company of Jakarta. Data intelligence, need achievement and performance were found from personnel data in organization. Based on regression analysis concluded that 1) there was a significant correlation between intellectual ability and need achievement with work performance, 2) there was no correlation between intellectual ability and work performance, 3) there was a significant positive correlation between need achievement and work performance.